2019
DOI: 10.1186/s13173-019-0093-7
|View full text |Cite
|
Sign up to set email alerts
|

Testing tools for Android context-aware applications: a systematic mapping

Abstract: Context: Mobile devices, such as smartphones, have increased their capacity of information processing and sensors have been aggregated to their hardware. Such sensors allow capturing information from the environment in which they are introduced. As a result, mobile applications that use the environment and user information to provide services or perform context-based actions are increasingly common. This type of application is known as context-aware application. While software testing is an expensive activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 98 publications
(147 reference statements)
0
3
0
1
Order By: Relevance
“…Untuk memvalidasi secara otomatis jawaban mahasiswa, APLAS menggunakan dua alat pengujian, JUnit (Jain & Gopalani, 2017) H a l a m a n | 123 aplikasi Android, seperti tata letak UI, activity, event listener, dan resource (Almeida et al, 2019).…”
Section: Validasi Jawaban Mahasiswaunclassified
“…Untuk memvalidasi secara otomatis jawaban mahasiswa, APLAS menggunakan dua alat pengujian, JUnit (Jain & Gopalani, 2017) H a l a m a n | 123 aplikasi Android, seperti tata letak UI, activity, event listener, dan resource (Almeida et al, 2019).…”
Section: Validasi Jawaban Mahasiswaunclassified
“…An automatic testing tool is essential to implement the automated assessment or validation of source codes. Almedia et al showed that JUnit and Robolectric are widely used testing tools in Android programming [16].…”
Section: B Android Librarymentioning
confidence: 99%
“…To implement the automatic assessment or validation, the application of an automatic testing tool appears to be essential. The study of Almedia et al showed that JUnit and Robolectric are the widely used testing tools in Android programming [34]. In the applications of unit testing, JUnit is leveraged to automate the creation of unit testing cases [35].…”
Section: Unit Testing Toolsmentioning
confidence: 99%